Analisis Isra’iliyyat Dalam Tafsir Hasyiah Al-Sawi Karya Ahmad Bin Muhammad Sawi Al-Maliki - Lumngatul Maarif; Eka Prasetiawati (Institut Agama Islam Negeri (IAIN) Curup, 2020)
This paper examines the view of Imam Sawi towards isra'iliyyat in the interpretation of the mustyiah mustard. The inclusion of isra'iliyyat in Islam began in the era of the Prophet, but that period was still counted by the Prophet. After he died, the entry of Israel became increasingly out of control. In the tabi'in era and later generations, many commentators have included isra'iliyyat in their interpretations even today. The method in this research is descriptive-analytical with content analysis for data analysis. In this study, 12 stories which are categorized as isra'iliyyat are displayed. From this research,Sawi's view of isra'iliyyatcould be analyzed.At some point,he gives comments, and he is also silent to some extent. Of the 12 stories that are displayed, there are 3 stories that get comments while the rest is without comments. Those who received comments were the story of Joseph and Zulaikha, the son of Ibrahim who was slain and the story of Zainab bint Jahsyi. From these results, it can be concluded that Sawi is a productive and critical writer, while the israiliyyat shown may be ibrah. As for not commenting, because of the nature of tawadhu'he was a great Sufi from the Tariqah Khalwatiyah.